2020
DOI: 10.1101/2020.04.16.044487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two dynamically distinct circuits driving inhibition in sensory thalamus

Abstract: Most sensory information destined for the neocortex is relayed there from the thalamus, where considerable transformation occurs 1,2 . One powerful means of transformation involves interactions between excitatory thalamocortical neurons that carry data to cortex and inhibitory neurons of the thalamic reticular nucleus (TRN) that regulate flow of those data 3-6 . Despite enduring recognition of the TRN's importance 7-9 , understanding of its cell types, their organization, and their functional properties has la… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 47 publications
5
15
0
Order By: Relevance
“…Using immunohistochemistry and confocal imaging, we confirmed that putative synaptic boutons from PV and SST nRT neurons are largely distinct (Figure 1-figure supplement 2), although certain neurons do express both markers (Figure 1-figure supplement 2) consistent with previous work (Clemente-Perez et al, 2017). Calbindin has been suggested as another marker of a subpopulation of nRT neurons (Martinez-Garcia et al, 2020); however, this has not been confirmed by single-nuclear RNA sequencing studies, which found no absolutely exclusive genetic markers between nRT cell types, although gradients in Spp1 and Ecl1 gene expression were noted between core and shell parts of the nRT (Li et al, 2020). Future studies at multiple levels of analysis (protein, genetic) will determine whether the differences between results of the studies cited above are due to use of different transgenic mouse models.…”
Section: Cellular Heterogeneity In the Nrtsupporting
confidence: 83%
See 1 more Smart Citation
“…Using immunohistochemistry and confocal imaging, we confirmed that putative synaptic boutons from PV and SST nRT neurons are largely distinct (Figure 1-figure supplement 2), although certain neurons do express both markers (Figure 1-figure supplement 2) consistent with previous work (Clemente-Perez et al, 2017). Calbindin has been suggested as another marker of a subpopulation of nRT neurons (Martinez-Garcia et al, 2020); however, this has not been confirmed by single-nuclear RNA sequencing studies, which found no absolutely exclusive genetic markers between nRT cell types, although gradients in Spp1 and Ecl1 gene expression were noted between core and shell parts of the nRT (Li et al, 2020). Future studies at multiple levels of analysis (protein, genetic) will determine whether the differences between results of the studies cited above are due to use of different transgenic mouse models.…”
Section: Cellular Heterogeneity In the Nrtsupporting
confidence: 83%
“…The existence of functionally distinct neuron types within the nRT has been shown (Lee et al, 2007;Halassa et al, 2014), and has recently been associated with PV and SST markers (Clemente-Perez et al, 2017), and further extended to additional molecular markers (Li et al, 2020;Martinez-Garcia et al, 2020). Finding molecular markers of functionally distinct nRT cells may be significant because it could allow us to selectively perturb distinct functions of the nRT.…”
Section: Cellular Heterogeneity In the Nrtmentioning
confidence: 97%
“…Notably, the zona incerta has reciprocal connections with the initiation site and when inhibited, reduces SWD occurrence (Liang et al, 2011;Shaw et al, 2013). Although S1 has been shown to affect VB neurons via the NRT during SWD (McCafferty et al, 2018) this cannot be generalized to the PO since NRT microcircuits between FO and HO differ in their location and properties (Martinez-Garcia et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These neurons had also significantly lower firing and burst rates and were spatially mixed with the neurons which showed significant correlation with the cortical LFP (FigS4). Recent investigations (Clemente-Perez et al, 2017; Li et al, 2020; Martinez-Garcia et al, 2020) demonstrated the presence of at least two morphologically and physiologically different cell types in the TRN. Whether the two anterior TRN populations in our experiments corresponds with these previously described groups requires further investigation.…”
Section: Discussionmentioning
confidence: 99%